Understanding about pap smear among Malay women - Mohamad Diah, Nurazzura; Saad, Nurulwahida; Mustari, Sohela (2015)
The purpose of this study is to assess the knowledge, attitudes, practices and cultural beliefs of urban Malay (Muslim) women towards Pap smear screening. A questionnaire-based survey of 300 Malay women in the Gombak district of Selangor, Malaysia, which evaluated the socio-demographic characteristics of respondents, knowledge of Pap smear testing, attitudes and cultural beliefs was distributed. Generally, the findings reveal that respondents had a good understanding of the purpose of Pap smear screening with 82.7% knowing that it can detect the early development of cervical cancer and 64% understanding that Pap smears can detect human papillomavirus (HPV) or other sexually transmitted infections (STI). 70% of the respondents believed that Pap smears are recommended to women who are married and 44.6% believed that Pap smears are recommended only to those who have had children. Generally, the respondents possessed good knowledge of Pap smear screening and its purpose. However, Malay cultural and religious beliefs and attitude regarding sexual activity and women's chastity directs that only those who are married with children are recommended for Pap smear screening. This cultural belief may be what contributes to low participation in Pap smear screening programmes.